2020
DOI: 10.1002/cbic.202000020
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Diversity of Plant Monoterpenoid Indole Alkaloids Employing Human Cytochrome P450 3A4

Abstract: Human drug‐metabolizing cytochrome P450 monooxygenases (CYPs) have enormous substrate promiscuity; this makes them promising tools for the expansion of natural product diversity. Here, we used CYP3A4 for the targeted diversification of a plant biosynthetic route leading to monoterpenoid indole alkaloids. In silico, in vitro and in planta studies proved that CYP3A4 was able to convert the indole alkaloid vinorine into vomilenine, the former being one of the central intermediates in the ajmaline pathway in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…We detected TA N-oxygenation only by the PNO derived from the omniherbivorous Z. variegatus, consistent with its need to detoxify a broader range of dietary plant alkaloids relative to specialist herbivores (50,53). Our results contribute to a growing body of evidence that enzymes used for PNP detoxification can be co-opted to expand biosynthetic diversity in engineered hosts (61).…”
Section: Discussionsupporting
confidence: 71%
“…We detected TA N-oxygenation only by the PNO derived from the omniherbivorous Z. variegatus, consistent with its need to detoxify a broader range of dietary plant alkaloids relative to specialist herbivores (50,53). Our results contribute to a growing body of evidence that enzymes used for PNP detoxification can be co-opted to expand biosynthetic diversity in engineered hosts (61).…”
Section: Discussionsupporting
confidence: 71%
“…Corey–Kim oxidation of 29 followed by a bioinspired cyclization (Scheme ) furnished the total synthesis of vinorine ( 1 ). The NMR spectra of our synthetic sample agree well with the reported data …”
supporting
confidence: 90%
“…The NMR spectra of our synthetic sample agree well with the reported data. 22 Table 1. Optimization of the Proposed Cyclization a entry oxidants (equiv), additives (equiv), and oxidation times, then Lewis acids (equiv) yields Reactions were conducted with 0.2 mmol of 14 in solvents (5 mL) at 0 °C to rt.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, there are few studies that consciously re-purpose human liver P450s as catalysts for the synthetic manipulation of natural products that are not necessarily of immediate pharmaceutical importance. Recently, Sheludko et al reported the successful diversification of an indole alkaloid intermediate in a plant natural product biosynthesis using P450 3A4 in vitro and in planta [37] and we obtained new insight into the degree of P450 3A4-catalysed diversification of the steroid testosterone during the preparative-scale synthesis of its metabolites using the monooxygenase in form of a whole-cell biocatalyst expressed in Pichia pastoris. [38] Encouraged by these studies, we hypothesised that this human P450 would not only accept, but also diversify a wide range of different natural products to a similar extent as the model substrate testosterone.…”
Section: Introductionmentioning
confidence: 68%